(untitled) (Minerva, 2020)
Review Rosario López Gregoris (ed.), Drama y dramaturgia en la escena romana. III Encuentro Internacional de Teatro Latino, Zaragoza, Libros Pórtico, 2019, 381 páginas, ISBN 978-84-7956-188-8